NEW RECORDS AND TAXONOMIC REEXAMINATION OF THE GENUS KELERIA (COPEPODA, POECILOSTOMATOIDA, LICHOMOLGIDAE) FROM INDONESIAN WATERS - Mulyadi (The East Java Biological Society, 2005)
Taxonomy and distribution were studied on the species of the family Lichomolgidae recently collected from 4 sites in Indonesian waters. Three species were recorded, including Kelleria pectinata (A. Scott, 1909) has been recorded previously from Indonesian waters, and Kelleria australiensis Bayly, 1971 and Kelleria regalis Gurney, 1927 were new records for the area. The distribution of these species in Indonesian waters and other regions in the world is compiled and discussed.